PENGARUH CURRENT RATIO DAN RETURN ON EQUTY TERHADAP DEBT TO EQUITY RATIO PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rahmat Hidayat; Dody Firman; Siti Kholijah Sarumpaet (Universitas Serambi Mekkah, 2019)
This study aims to determine how the Effect of Current Ratio and Return On Equity on Debt to Equity Ratio both partially and simultaneously in the Manufacturing of Food and Beverage sub-sectors listed on the Indonesia Stock Exchange for the period 2013-2017. The approach used is the Associative approach. The population in this study is a Food and Beverage sub- sector manufacturing company listed on the Indonesia Stock Exchange for the period 2013- 2017. Samples taken using purposive sampling technique to obtain 7 companies as samples. The data uses multiple linear regression analysis, Classical assumption test, t-test (Persial), F- Test (Simultaneous), and coefficient of determination using SPSS 16.0 software. Based on the test results it can be concluded that partially Current Ratio has a significant effect on Debt to Equity Ratio and Return On Equity does not affect the Debt to Equity ratio, while Simultaneously Current Ratio and Return On Equity have a significant effect on Debt to Equity Ratio. In the Manufacturing of Food and Beverage sub-sector companies listed on the Indonesia Stock Exchange for the period 2013-2017.